Both Hypoxia and Hypobaria Impair Baroreflex Sensitivity but through Different Mechanisms - Bourdillon, Nicolas; Aebi, Mathias Rolland; Kayser, Bengt; Bron, Denis; Millet, Gregoire P (International Journal of Sports Medicine, 2022)
Baroreflex sensitivity (BRS) is a measure of cardiovagal baroreflex and is lower in normobaric and hypobaric hypoxia compared to normobaric normoxia. The aim of this study was to assess the effects of hypobaria on BRS in normoxia and hypoxia. Continuous blood pressure and ventilation were recorded in eighteen seated participants in normobaric normoxia (NNx), hypobaric normoxia (HNx), normobaric hypoxia (NHx) and hypobaric hypoxia (HHx). Barometric pressure was matched between NNx vs. NHx (723±4 mmHg) and HNx vs. HHx (406±4 vs. 403±5 mmHg). Inspired oxygen pressure (PiO2) was matched between NNx vs. HNx (141.2±0.8 vs. 141.5±1.5 mmHg) and NHx vs. HHx (75.7±0.4 vs. 74.3±1.0 mmHg). BRS was assessed using the sequence method. BRS significantly decreased in HNx, NHx and HHx compared to NNx. Heart rate, mean systolic and diastolic blood pressures did not differ between conditions. There was the specific effect of hypobaria on BRS in normoxia (BRS was lower in HNx than in NNx). The hypoxic and hypobaric effects do not add to each other resulting in comparable BRS decreases in HNx, NHx and HHx. BRS decrease under low barometric pressure requires future studies independently controlling O2 and CO2 to identify central and peripheral chemoreceptors’ roles.
Keywords: baroreflex sensitivity; blood pressure; heart rate; hypobaria; hypoxia; hypocapnia